2018
DOI: 10.1016/j.ijscr.2018.10.040
|View full text |Cite
|
Sign up to set email alerts
|

A tourniquet-less technique using saline epinephrine irrigation system in an arthroscopic ACL reconstruction in patient with history of popliteal artery ligation

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
1
0
1
Order By: Relevance
“…Barium hidroksida adalah senyawa kimia dengan rumus kimia Ba (OH)2, yang mempunyai bentuk kristal putih (52)(53)(54)(55)(56)(57)(58)(59)(60)(61) Barium hidroksida ini memiliki sifat fisika (62)(63)(64)(65)(66)(67) dan sifat kimia seperti terlihat pada tabel di bawah ini. Barium merupakan suatu unsur kimia dalam tabel periodik yang memiliki lambang Ba dan nomor atom 56.Barium tidak ditemukan dialam dalam keadaan unsur bebas karena reaktivitas kimianya yang tinggi.Barium (68) secara kimiawi mirip dengan magnesium, kalsiumdan stronsium, namun lebih reaktif.…”
Section: Pembahasanunclassified
“…Barium hidroksida adalah senyawa kimia dengan rumus kimia Ba (OH)2, yang mempunyai bentuk kristal putih (52)(53)(54)(55)(56)(57)(58)(59)(60)(61) Barium hidroksida ini memiliki sifat fisika (62)(63)(64)(65)(66)(67) dan sifat kimia seperti terlihat pada tabel di bawah ini. Barium merupakan suatu unsur kimia dalam tabel periodik yang memiliki lambang Ba dan nomor atom 56.Barium tidak ditemukan dialam dalam keadaan unsur bebas karena reaktivitas kimianya yang tinggi.Barium (68) secara kimiawi mirip dengan magnesium, kalsiumdan stronsium, namun lebih reaktif.…”
Section: Pembahasanunclassified
“…A number of researches have been implemented to explore the efficiency of tourniquet on the prognosis after receiving ACLR. [ 16 , 17 , 18 , 19 , 20 ] Daniel et al confirmed that tourniquet applications at 12 weeks after operation can delay the recovery of quadriceps femoris strength and lead to more muscle atrophy, but there is no apparent difference at 52 weeks. [ 16 ] In the literature, a number of randomized studies on our subject are reported.…”
Section: Introductionmentioning
confidence: 99%